Oral administration of iron-saturated bovine lactoferrin–loaded ceramic nanocapsules for breast cancer therapy and influence on iron and calcium metabolism - Mahidhara G (Dove Medical Press, 2015)
Ganesh Mahidhara, Rupinder K Kanwar, Kislay Roy, Jagat R Kanwar Nanomedicine-Laboratory of Immunology and Molecular Biomedical Research, School of Medicine, Molecular and Medical Research Strategic Research Centre, Faculty of Health, Deakin University, Waurn Ponds, VIC, Australia Abstract: We determined the anticancer efficacy and internalization mechanism of our polymeric–ceramic nanoparticle system (calcium phosphate nanocores, enclosed in biodegradable polymers chitosan and alginate nanocapsules/nanocarriers [ACSC NCs]) loaded with iron-saturated bovine lactoferrin (Fe-bLf) in a breast cancer xenograft model. ACSC-Fe-bLf NCs with an overall size of 322±27.2 nm were synthesized. In vitro internalization and anticancer efficacy were evaluated in the MDA-MB-231 cells using multicellular tumor spheroids, CyQUANT and MTT assays. These NCs were orally delivered in a breast cancer xenograft mice model, and their internalization, cytotoxicity, biodistribution, and anticancer efficacy were evaluated. Chitosan-coated calcium phosphate Fe-bLf NCs effectively (59%, P≤0.005) internalized in a 1-hour period using clathrin-mediated endocytosis (P≤0.05) and energy-mediated pathways (P≤0.05) for internalization; 3.3 mg/mL of ACSC-Fe-bLf NCs completely disintegrated (~130-fold reduction, P≤0.0005) the tumor spheroids in 72 hours and 96 hours. The IC50 values determined for ACSC-Fe-bLf NCs were 1.69 mg/mL at 10 hours and 1.62 mg/mL after 20 hours. We found that Fe-bLf-NCs effectively (P≤0.05) decreased the tumor size (4.8-fold) compared to the void NCs diet and prevented tumor recurrence when compared to intraperitoneal injection of Taxol and Doxorubicin. Receptor gene expression and micro-RNA analysis confirmed upregulation of low-density lipoprotein receptor and transferrin receptor (liver, intestine, and brain). Several micro-RNAs responsible for iron metabolism upregulated with NCs were identified. Taken together, orally delivered Fe-bLf NCs offer enhanced antitumor activity in breast cancer by internalizing via low-density lipoprotein receptor and transferrin receptor and regulating the micro-RNA expression. These NCs also restored the body iron and calcium levels and increased the hematologic counts. Keywords: oral delivery, Fe-bLf, miRNA, xenograft, breast cancer